The impact of backbone N‐methylation on the structure‐activity relationship of Leu10‐teixobactin. (6th August 2019) - Velkov, Tony; Swarbrick, James D.; Hussein, Maytham H.; Schneider‐Futschik, Elena K.; Hoyer, Daniel; Li, Jian; Karas, John A.
Abstract : Antimicrobial resistance is a serious threat to global human health; therefore, new anti‐infective therapeutics are required. The cyclic depsi ‐peptide teixobactin exhibits potent antimicrobial activity against several Gram‐positive pathogens. To study the natural product's mechanism of action and improve its pharmacological properties, efficient chemical methods for preparing teixobactin analogues are required to expedite structure‐activity relationship studies. Described herein is a synthetic route that enables rapid access to analogues. Furthermore, our new N ‐methylated analogues highlight that hydrogen bonding along the N ‐terminal tail is likely to be important for antimicrobial activity. Abstract : Backbone N ‐methylation of Leu10 ‐teixobactin has a profound effect on its antimicrobial activity.